The functional role of soluble proteins acquired by extracellular vesicles. Issue 1 (16th March 2022) - Ramos, Ana Paula; Sebinelli, Heitor Gobbi; Ciancaglini, Pietro; Rosato, Nicola; Mebarek, Saida; Buchet, Rene; Millán, José Luis; Bottini, Massimo
Abstract: Extracellular vesicles (EVs) are lipid bilayer‐enclosed nanosized particles released by all cell types during physiological as well as pathophysiological processes to carry out diverse biological functions, including acting as sources of cellular dumping, signalosomes and mineralisation nanoreactors. The ability of EVs to perform specific biological functions is due to their biochemical machinery. Among the components of the EVs' biochemical machinery, surface proteins are of critical functional significance as they mediate the interactions of EVs with components of the extracellular milieu, the extracellular matrix and neighbouring cells. Surface proteins are thought to be native, that is, pre‐assembled on the EVs' surface by the parent cells before the vesicles are released. However, numerous pieces of evidence have suggested that soluble proteins are acquired by the EVs' surface from the extracellular milieu and further modulate the biological functions of EVs during innate and adaptive immune responses, autoimmune disorders, complement activation, coagulation, viral infection and biomineralisation. Herein, we will describe the methods currently used to identify the EVs' surface proteins and discuss recent knowledge on the functional relevance of the soluble proteins acquired by EVs.